1999
DOI: 10.1097/00005344-199904000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Temocapril in Hypertensive Patients with Diabetes Mellitus Type 2

Abstract: Compared with other angiotensin-converting enzyme (ACE) inhibitors, the elimination of temocapril is less dependent on renal function. To investigate the metabolic and antihypertensive effects of temocapril in diabetic hypertensives, 30 patients with diabetes mellitus type 2 and mild to moderate hypertension [diastolic blood pressure (BP) 90-115 mm Hg] and without azotemia (plasma creatinine < 180 microM) were evaluated in a prospective randomized double-blind placebo-controlled study. After a 4-week placebo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…We confirm previous reports of neutral effects on total cholesterol and triglycerides with both the ACE inhibitor and CCB. [31][32][33] We also corroborate a previous report that indicated small increases in HDL-cholesterol with an ACE inhibitor. 34 More importantly, we noted, that HDLcholesterol also rose with the use of the ACE inhibitor/CCB combination.…”
Section: Discussionsupporting
confidence: 90%
“…We confirm previous reports of neutral effects on total cholesterol and triglycerides with both the ACE inhibitor and CCB. [31][32][33] We also corroborate a previous report that indicated small increases in HDL-cholesterol with an ACE inhibitor. 34 More importantly, we noted, that HDLcholesterol also rose with the use of the ACE inhibitor/CCB combination.…”
Section: Discussionsupporting
confidence: 90%
“…In hypertensive Type 2 diabetic patients, captopril increased insulin-mediated glucose uptake by 30% [77]. Although other authors also reported minor beneficial effect on glucose metabolism [78,79], these effects of ACEI have not been confirmed by other groups [80][81][82][83][84]. Some studies have also reported beneficial effects of ACEI on plasma lipid levels [78,82,[84][85][86].…”
Section: Effects Of Acei On Insulin Sensitivity In Type 2 Diabetesmentioning
confidence: 97%
“…On the other hand, significantly more patients in the enalapril group were treated with the combination of antihypertensive agents including the β-blocker and diuretic. The analysis included both patients assigned for intensive blood pressure treatment aiming at target diastolic pressure 75 mmHg and patients assigned to moderate pressure control (80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Importantly, the difference in incidence of MI lead investigators to a decision to terminate the nisoldipine treatment in hypertensive NIDDM patients and the follow-up continues only in normotensive patients.…”
Section: Studies With Primarily Cardio-and Cerebrovascular End-pointsmentioning
confidence: 99%
“…There is some evidence that ACE inhibitors have a modest beneficial effect on insulin sensitivity and this could be an added bonus of ACE inhibitor treatment[112–114]. However, in several placebo controlled trials no beneficial effect of ACE inhibitors on insulin sensitivity has been found[115–117] and the controversy is still ongoing. In this context also the mechanism whereby ACE inhibitors may modulate insulin effectiveness on glucose disposal remain unclear.…”
Section: Chf Therapy and Insulin Resistancementioning
confidence: 99%